Η2‐Coordination of a Phosphaalkyne to an Amino Olefin Nickel Complex and Regioselective Catalyzed Cyclooligomerization to Dewar 1, 3, 5‐Triphosphabenzene. Issue 10 (14th October 2013) - Trincado, Mónica; Rosenthal, Amos J.; Vogt, Matthias; Grützmacher, Hansjörg
Abstract: We report herein an efficient synthesis of a Dewar‐triphosphabenzene derived from [2+2+2] cycloaddition of three phosphaalkyne molecules promoted by an amino olefin Ni 0 complex as the catalyst. Amino diolefin Ni I complex1 serves as a precursor complex that reacts with triphenylmethylphosphaethyne under reducing conditions at low temperature to give Ni 0 complex3 with a coordinated phosphaalkyne in a η 2 ‐mode. The structure of3 was determined by X‐ray diffraction methods and suggests a bonding situation for the phosphaalkyne that is between a side‐on coordinated C≡P molecule and a metallaphosphacyclopropene structure. The reaction of3 with a 10‐fold excess of phosphaethylene under reducing conditions at room temperature resulted in the formation of 2, 4, 6‐tris(triphenylmethyl)‐Dewar‐1, 3, 5‐triphosphabenzene (4 ) in good yield. Abstract : A preorganized tridentate diolefin amine ligand coordinated to a nickel atom provides the required stability to the zero‐valent metal center. The hemilability of the olefin binding sites allows side‐on coordination of a phosphaalkyne and successive head‐to‐tail coupling of up to three molecules to afford a cyclic Dewar‐1, 3, 5‐phosphaalkyne with liberation of the heterocycle under a catalytic regime.